1997
DOI: 10.1046/j.1365-2796.1997.98108000.x
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol and coronary heart disease: the roles of HDL‐cholesterol and smoking

Abstract: Abstract. Man$ tta$ ri M, Tenkanen L, Alikoski T, Manninen V (Department of Medicine, Helsinki University and Helsinki Heart Study, Helsinki, Finland). Alcohol and coronary heart disease : the roles of HDL-cholesterol and smoking. J. Intern Med 1997 ; 241 : 157-63. Objectives.To study the role of HDL-cholesterol (HDLc) in the causal pathway mediating the effect of alcohol on coronary heart disease (CHD). Design. Cox proportional hazard models were used to compare the relative CHD risks in various HDLcsmoking c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 31 publications
(45 reference statements)
0
15
1
Order By: Relevance
“…Although several significant reviews have documented the occurrence of U-shaped dose-responses in biological and toxicological systems (9,10,17,18,22), such responses have also been commonly seen in numerous pharmacological investigations (8) as well as for endpoints of considerable public health significance, including body weight and longevity (1-3, 20, 30, 36, 40, 48, 62, 63, 80-83, 89), cholesterol and longevity (28, 47), alcohol consumption and cardiovascular disease incidence (33,49,50,52,54,56), and exercise intensity/duration and immune responsive disease resistance (6,29,39,53,57,71). The occurrences of U-shaped dose-responses are thus widely and independently observed phenomena.…”
Section: Publications With U-shaped Dose-responsesmentioning
confidence: 99%
“…Although several significant reviews have documented the occurrence of U-shaped dose-responses in biological and toxicological systems (9,10,17,18,22), such responses have also been commonly seen in numerous pharmacological investigations (8) as well as for endpoints of considerable public health significance, including body weight and longevity (1-3, 20, 30, 36, 40, 48, 62, 63, 80-83, 89), cholesterol and longevity (28, 47), alcohol consumption and cardiovascular disease incidence (33,49,50,52,54,56), and exercise intensity/duration and immune responsive disease resistance (6,29,39,53,57,71). The occurrences of U-shaped dose-responses are thus widely and independently observed phenomena.…”
Section: Publications With U-shaped Dose-responsesmentioning
confidence: 99%
“…Well known factors that have a beneficial effect on the abundance of apo AI protein include: physical excercise (Huttunen et al 1979, Ballantyne et al 1982, Danner et al 1984, alcohol consumption (McConnell et al 1997, Manttari et al 1997) and being female (Heiss et al 1980). These factors increase concentrations of apo AI protein.…”
Section: Introductionmentioning
confidence: 99%
“…However, in a Finnish study 35 with a limited number of cardiovascular events analyzed, the authors observed that the protective effect associated with alcohol consumption was limited to smokers. This may be explained by the highest absolute risk in smokers, which increases the potential benefits of protective factors.…”
Section: Effects Of Alcohol On Cardiovascular Risk Factorsmentioning
confidence: 97%
“…Population-based evidence shows higher levels of HDL-C in individuals drinking alcoholic beverages 35,36 . However, only 50% of the protective effect may be explained by an increase in HDL-C 28 .…”
Section: Effects Of Alcohol On Cardiovascular Risk Factorsmentioning
confidence: 99%